Left hemispatial neglect with a splenial lesion. Issue 4 (4th July 2018) - Kesayan, Tigran; Gasoyan, Hamlet; Heilman, Kenneth M.
ABSTRACT: With injury of the anterior two-thirds of the corpus callosum, each hemisphere's attentional bias to contralateral hemispace becomes manifest with each hand deviating ipsilaterally during line bisection tasks. Patients with infarctions in the right posterior cerebral artery distribution with occipital and splenial damage can also exhibit spatial neglect. The goal of this report is to learn the role of the splenium of the corpus callosum in mediating visuospatial attention. A right-handed woman with Marchiafava-Bignami disease and damage to the splenium of her corpus callosum without evidence of a mesial frontal, parietal, or occipital injury was assessed for spatial neglect with line bisections. When bisecting lines in her left hemispace with her right hand, she deviated to the right, but revealed no major deviations when the line was place in the midline, in right hemispace, or when bisecting lines with her left hand. This patient provides evidence that damage to the splenium can induce a special form of asymmetrical spatial neglect. This asymmetry might be related to the disconnected right hemisphere's ability to allocate attention to both right and left hemispaces with the disconnected left hemisphere's ability to allocate attention to the right but not left hemispace.